Preliminary study of the Peruvian Amazon ichthyoplankton with emphasis on the Pimelodidae family - Rojas, María (2006)
This paper is a report of ichthyoplankton community and the description of ﬁsh larvae from the beginning of River Madre de Dios, in special on the family Pimelodidae. The collections were carried out between November and December of 2004, utilizing a ichthyoplankton net (300 microns of mesh), in 8 transects that covered an approximate section of 2 km upstream and downstream of the Puerto Maldonado city. A total of 83750 larvae were examined, the highest abundance was displayed by Characiformes (81%), followed by Siluriformes (18%). In the Pimelodidae family, 12 commercial species of consumption, emphasizing Pseudoplatystoma tigrinum, P. fasciatum y Sorubim lima. The main orders in ichthyoplankton follow a pattern of relative abundance similar to the adult state. The presence of larvae of great catﬁshes migratory (Pimelodidae family) in the zone of sampling suggests this region of the River Madre de Dios represents an area for reproduction, and therefore important for the conservation of these species.